(untitled) (Proceeding of the International Conference on Arts and Humanities, 2024)
This research study is a form of qualitative action research that aims to explore the benefits of in-class flipped learning as a means to enhance student cultural competence in an American Culture course. It was conducted at a university in Vietnam, where the recent COVID-19 pandemic introduced unprecedented online courses for education. However, blending online and offline instructional methods in the classroom was relatively easy for students, contrary to the initial concerns of the stakeholders and society. The instructor implemented in-class flipped instruction to improve the cultural competence of undergraduate business majors in an American Culture course. The focus was on enhancing students’ knowledge and perspectives on cultures and learner autonomy through technology. The study was conducted for a semester, and each lesson plan was designed to achieve these objectives. The students had access to a textbook as a reference to explore further. The course created an insightful and collaborative learning environment based on qualitative analysis of the interviews, class observations, and students’ work, including weekly assignments and end-of-semester group projects. The study found that college students can quickly improve their mindset with proper guidance and resources. This can be achieved by increasing interactions between students and instructors and transforming learners’ mindsets on their responsibility for learning. Overall, this research study shows that in-class flipped learning can effectively enhance cultural competence among students, particularly in courses related to cultural studies and business. It also highlights the importance of creating an interactive and collaborative learning environment to facilitate student learning and development.